1994
DOI: 10.1242/jeb.192.1.129
|View full text |Cite
|
Sign up to set email alerts
|

Undulatory Swimming: How Traveling Waves are Produced and Modulated in Sunfish (Lepomis Gibbosus)

Abstract: We have developed an experimental procedure in which the in situ locomotor muscles of dead fishes can be electrically stimulated to generate swimming motions. This procedure gives the experimenter control of muscle activation and the mechanical properties of the body. Using pumpkinseed sunfish, Lepomis gibbosus, we investigated the mechanics of undulatory swimming by comparing the swimming kinematics of live sunfish with the kinematics of dead sunfish made to swim using electrical stimulation. In electrically … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

1997
1997
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(15 citation statements)
references
References 24 publications
0
15
0
Order By: Relevance
“…It tackles the similar problem of singlepoint actuated compliant tails [38] and uses the findings in [39,40] to present a general framework for modelling and validating the dynamics of the compliant part. This design approach is inspired by studies in which electromyography muscle activity measurements of swimming fish have revealed that for swimming at cruising speeds (1 to 2 body length s −1 ) fish use mainly anterior muscles while the posterior part of the body carries the travelling wave passively to transfer the momentum to the surrounding fluid [31][32][33]. Other studies emphasize the importance of the material properties of fish (in particular stiffness) in determining the operating frequency of the fish body and tail [34,35].…”
Section: Introductionmentioning
confidence: 99%
“…It tackles the similar problem of singlepoint actuated compliant tails [38] and uses the findings in [39,40] to present a general framework for modelling and validating the dynamics of the compliant part. This design approach is inspired by studies in which electromyography muscle activity measurements of swimming fish have revealed that for swimming at cruising speeds (1 to 2 body length s −1 ) fish use mainly anterior muscles while the posterior part of the body carries the travelling wave passively to transfer the momentum to the surrounding fluid [31][32][33]. Other studies emphasize the importance of the material properties of fish (in particular stiffness) in determining the operating frequency of the fish body and tail [34,35].…”
Section: Introductionmentioning
confidence: 99%
“…In longnose gar ( Lepisosteus osseus ), artificially reducing stiffness caused fish to lower their tail-beat frequency ( 44 ). In pumpkinseed sunfish ( Lepomis gibbosus ), reducing stiffness led to lower swimming speeds at the same tail-beat frequency ( 45 ). Only by tuning stiffness could our platform and Tunabot maintain a linear frequency-speed relation and a plateaued frequency-efficiency relation using a single gait (Figs.…”
Section: Discussionmentioning
confidence: 99%
“…The fish body may be treated as a simple beam, whereby the axial waveform is subject to the passive mechanics of the body (Long et al, 1994; Long & Nipper, 1996). Specifically, a wave passing through a body of relatively high flexural stiffness ( M ) will lengthen while one passing through low M will shorten.…”
Section: Methodsmentioning
confidence: 99%